Genome-wide association study and marker validation to enhance yellow color in durum wheat - Cabas-Lühmann, Patricia; Dreisigacker, Susanne; Ammar, Karim; Megerssa, Shitaye H.; Schwember, Andrés Ricardo; Matus, Iván; Ibba, Maria Itria (Elsevier, 2025)
Yellow color in durum wheat (Triticum turgidum spp. durum) is a complex trait controlled by multiple genes. This study aimed to validate both existing and novel molecular markers, as well as to identify new genomic regions associated with yellow index (YI) measured by colorimeter CIE b∗ values in whole wheat flour and semolina of durum wheat. Allelic variants were identified at the Psy1-A1 and Psy1-B1 loci using gene-based molecular markers, while both genes showed close phylogenetic relationships and low sequence diversity across Triticum species. The 269 evaluated durum wheat lines showed high heritability (H2) for YI in both whole wheat flour and semolina. ANOVA showed that 8 out of the 13 tested gene-based markers were significant (P ≤ 0.05) for YI. Genome-wide association study (GWAS) could not confirm the gene-based marker significance, however, identified two stable marker-trait associations on chromosomes 5B (S5B_386629088) and 7A (S7A_694027001), explaining 46.7 % and 32.6 %, and 8.9 % and 11.1 % of phenotypic variance for whole wheat and semolina YI, respectively. The two regions were reported in prior studies, reinforcing their role in controlling semolina yellowness. Putative candidate genes located near the significant SNPs include an E3 ubiquitin-protein ligase and a senescence-associated family protein (DUF581), both potentially involved in carotenoid synthesis. However, further analysis are required to confirm their involvement. Two Kompetitive Allele-Specific PCR (KASP) markers were developed and validated to affect YI. Our results provide valuable insights targeting marker-assisted selection to enhance yellow pigment content in durum wheat.